Factors associated with poor attendance at the postpartum clinic six weeks after delivery in Cameroon. Issue 3 (June 2015) - Nkwabong, Elie; Ilue, Elisabeth E.; Bisong, Calvin E.
Abstract Objective To identify reasons why women do not attend the 6-week postpartum clinic in Cameroon. Methods A retrospective cross-sectional cohort survey was undertaken among women who had delivered at the University Teaching Hospital in Yaoundé between November 15 and December 31, 2013. Their medical files were retrieved and reviewed. Women who had not attended the 6-week postpartum clinic were contacted by telephone 2 months after delivery to establish reasons for non-attendance. Results Among 120 included women, 85 (70.8%) did not attend the 6-week postpartum clinic. Compared with women who had attended the 6-week visit, more women who had not attended the visit had delivered vaginally, had no postpartum complications, and had not been counseled to attend the visit (P < 0.001 for all). The main reason given for not attending this clinic was the feeling of well-being (n = 36 [42.4%]). Conclusion The benefits of attending the 6-week postpartum clinic should be emphasized in Cameroon, especially to women who have experienced uncomplicated vaginal delivery.